Социальная напряженность и тревожность в контексте диагностики общественных конфликтов - Бузовский, И. (Социология: теория, методы, маркетинг, 2008)
The article explores theoretical aspects of the social anxiety. Special attention is paid to social, psychological and sociopsychological factors conducive to the occurrence and development of this phenomenon, as well as its place and role in social processes.